Potential of Red Ginger Rhizome (Zingiber officinale Roscoe var. Rubrum) as an Anti-Cancer: A Review - Anggara, I Gede Yudi; Kirtishanti, Aguslina; Gondokesumo, Marisca E. (Universitas Padjadjaran, Indonesia, 2024)
Red ginger rhizome, Zingiber officinale Roscoe var. Rubrum has long been used as a herbal medicine. Its biological properties, including anti-cancer properties, are confirmed. Compared to their stems and leaf tissues, the average amount of gingerols in red ginger rhizomes (104.39 μg/g) is much higher. In addition to gingerol, other nonvolatile pungent chemicals found in ginger include shogaols, paradols, gingerdiols, and zingerone. Gingerol disrupts the cell cycle, triggers apoptosis in cancer cells, and prevents the growth and spread of cells by interacting with particular proteins, gene targets, and signal transduction pathways. 6-shogaol activity suppresses NF-kB and signal transducer and activator of transcription 3 (STAT3), decreases Bcl-2 expression, and increases Bax expression, which contributes to lowering cell viability and causing autotosis. The several functions of red ginger in regulating biological processes linked to anticancer effects will be outlined in this review. In order to organize related study findings in accordance with the specified publication criteria, this literature review employs a narrative technique. The chemical composition of red ginger rhizome that functions as an anti-cancer agent contains 6-gingerol, 6-shogaol, 10-gingerol, 6-paradon, and zingeron, according to the findings of this literature review that was conducted. Red ginger rhizome has been proven to have anti-cancer activity in various types of cancer that have been studied in vitro and in silico, there are head and neck cancer, endometrial adenocarcinoma,breast cancer, lung cancer, skin cancer, colon cancer, prostate cancer, leukemia, oral and cervical cancer, brain tumor, bone cancer, and pancreatic cancer.